Rasgrp1 deficiency associated with diffuse mesangial sclerosis infantile nephrotic syndrome and Epstein-Barr virus-induced Hodgkin’s lymphoma - Mohamed Nashrudin, Khairoon Nisa; Zainal Abidin, Mohd Azri; Ng, Shi Eng; Razali, Hadibiah; Jawin, Vida; Zakaria, Atiqah Farah; Mohd Ali, Razana; Othman, Ida Shahnaz; Mohamed Unni, Mohamed Najib; Hung, Christina Yuh-Ron; Ismail, Intan Hakimah (Mary Ann Liebert, 2025)
RASGRP1 deficiency is characterized by immune dysregulation and Epstein-Barr virus (EBV)-related lymphoproliferation. Diffuse mesangial sclerosis is one of the infrequent causes of infantile nephrotic syndrome. Here, we described a 7-year-old girl who was diagnosed with diffuse mesangial sclerosis at 5 months old and subsequently developed chronic bilateral neck swelling at the age of 3 years. Clinical assessment and investigations revealed a complex clinical picture, including recurrent cervical lymphadenopathy and recurrent infections. Further evaluation revealed immunological deficiencies, autoimmune lymphoproliferative syndrome-like illness, chronic EBV infection, and ultimately Hodgkin lymphoma. Genetic testing identified a RASGRP1 homozygous loss-of-function variant with both parents being carriers. This is the first reported case of RASGRP1 deficiency in Malaysia and we highlight the challenges clinicians face when the disease manifests in varied presentations.